2023
DOI: 10.1371/journal.pbio.3001930
|View full text |Cite
|
Sign up to set email alerts
|

Similar object shape representation encoded in the inferolateral occipitotemporal cortex of sighted and early blind people

Abstract: We can sense an object’s shape by vision or touch. Previous studies suggested that the inferolateral occipitotemporal cortex (ILOTC) implements supramodal shape representations as it responds more to seeing or touching objects than shapeless textures. However, such activation in the anterior portion of the ventral visual pathway could be due to the conceptual representation of an object or visual imagery triggered by touching an object. We addressed these possibilities by directly comparing shape and conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 126 publications
0
3
1
Order By: Relevance
“…Chinese characters were selected from the school textbook of Chinese first graders. Chinese word frequency (range=11-1945 occurrences per million, mean=326, SD=451 ( 52 )) was not significantly different from French words used here (t(38)=0.2, p=0.87). Single-digit formula stimuli were 3-character simple operations in the form of “x+y” or “x-y” with x greater than y, x ranging from 2 to 5, and y from 1 to 4.…”
Section: Methodscontrasting
confidence: 65%
See 1 more Smart Citation
“…Chinese characters were selected from the school textbook of Chinese first graders. Chinese word frequency (range=11-1945 occurrences per million, mean=326, SD=451 ( 52 )) was not significantly different from French words used here (t(38)=0.2, p=0.87). Single-digit formula stimuli were 3-character simple operations in the form of “x+y” or “x-y” with x greater than y, x ranging from 2 to 5, and y from 1 to 4.…”
Section: Methodscontrasting
confidence: 65%
“…The latter areas overlap with those active during the comprehension of elementary and advanced mathematical concepts ( 9 , 26 , 27 ), in agreement with their proposed involvement in an abstract, modality-independent symbolic encoding. Further support for this idea comes from the fact that these regions can be equally activated in sighted and in blind individuals, whether they perform mathematics ( 36 , 37 ) or just process the shapes of manmade objects ( 38 ). Thus, shape representation in these regions is amodal and more abstract than a hierarchy of visual filters.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital sensory deprivation constitutes a unique model to dissect the differential contribution of specific sensory modalities to the brain representation of the external world accounting for mental imagery (27). In this regard, previous studies comparing typically developed and sensory-deprived individuals have consistently shown that the brain code for animacy (28,29), spatial layout (30), and shape (31), among others, is primarily driven by specific computations rather than by modality or previous sensory experience (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies evaluating the within-category organization of object knowledge is considerably lower -that is, studies investigating how information is represented among basic level members of a single domain (e.g., within the domain of manipulable objects, how is information represented among the different basic level members such as a knife and a pair of scissors; (Gotts et al, 2011;Connolly et al, 2012;Bruffaerts et al, 2013;Bracci et al, 2017;Almeida et al, 2023aAlmeida et al, , 2023bXu et al, 2023). This is at odds with the fact that the hardest and perhaps most common everyday decisions we tend to make (e.g., is the object in front of us a knife or a fork) typically rely on finergrained, within-category representations.…”
Section: Introductionmentioning
confidence: 99%